Towards modern sustainable construction materials: a bibliographic analysis of engineered geopolymer composites - Zhang, Yin; Li, Huihong; Gamil, Yaser; Iftikhar, Bawar; Murtaza, Haseeb (Frontiers in Materials, 2023)
Engineered cementitious composite (ECC) exhibits impressive tensile strength but has significant environmental drawbacks due to high cement consumption. Recently, engineered geopolymer composites (EGC) have gained attention as a potential ECC alternative. This comprehensive study reviews the latest EGC advancements, encompassing mix design, design theory, engineering properties, environmental benefits, and durability. It emphasizes how factors like activators, precursors, fibers, additives, and aggregates impact EGC properties, making it a cost-effective material for fire, chemical resistance, and dynamic loads. To address limitations in traditional literature reviews, innovative research methods, including scientometric analysis, were employed to provide a cohesive analysis. This review aims to facilitate knowledge dissemination and collaboration by summarizing EGC advances and highlighting remaining challenges in developing practical applications. It is revealed from the review that various manufacturing methods enhance geopolymers, especially in geopolymer concrete, where replacing 50% of ordinary Portland cement with fly ash boosts strength. Geopolymer concrete excels in pre-cast applications, offering durability and resistance to harsh conditions as an eco-friendly alternative to Portland cement. It suits highway pavement, walls, marine coatings, and tiles, reducing carbon emissions and promoting efficient waste management. EGCs find broad use in construction due to their strong, durable, and eco-friendly qualities, supporting sustainable infrastructure development.